Role of Notary in the Making of A Powerful Legal Entire Property Distribution Deed - Hawwa Hauro; Widayati Widayati (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The distribution of inheritance using a notary deed is an alternative method of inheritance distribution in addition to using court institutions which are commonly used by Indonesian people in inheritance distribution. This writing aims to analyze the theory of the implementation of the distribution of inheritance and the evidentiary process in order to get full evidence in the District Court. The research method used in this thesis is a sociological juridical approach, namely legal research carried out by examining how reactions and interactions occur because legal expectations are often different from the reality that occurs in society, or it can be called the gap between Das Sein (facts) and Das Sollen (norms/expectations). This study was analyzed using the theory of justice in Islam, the theory of legal certainty, and the theory of proof. The results of the study found that the theoretical analysis of the implementation of the distribution of inheritance, both according to the distribution of Islamic inheritance and the Civil Code already has legal certainty.The power of proof attached to an authentic deed is perfect strength and means that the proof is sufficient with the deed itself unless there is opposing evidence (tegen bewijs) which proves otherwise or proves otherwise from the deed. A deed according to the formulation of Article 1868 of the Civil Code, to obtain authenticity as an authentic deed, must meet several requirements, namely: the deed is made by or before a public official; the deed must be made in the form determined by law; and the public official must have the authority to make a deed.